ANALYSIS OF CRIMINOGEN DETERMINANTS IN CHILDREN CLIENTS - Rizki Ayu Hanifah (Polteknik Ilmu Pemasyarakatan, 2018)
This study aims to describe the influence between the level of social bonding on child mischief on child clients in Probation Boards Class I Bandung. The type of research is descriptive to describe and explain the influence of social bonding level to child mischief on child client in Probation Boards Class I Bandung. The test is done by measuring the dimension of social bonding as stated by Hirschi, that is Attachment, Commitment, Involvment, and Belief. This study uses a quantitative approach. This study describes the influence of social bonding level on child mischief on child clients in Probation Boards. The sampling process of the researh was done by total sampling technique. After sampling, we get 501 Litmas documents of children. Data collection was done by several techniques, namely content analysis, and literature study. Management of data obtained from the content analysis, and literature study. Management of data obtained from the contents of litmas that have been inserted into the coding is done by using SPSS 20 program. Based on the results of research that has been done by the author for 3 weeks at Probation, that the level of social bonding on child clients in Probation is at a low level. So it can be concluded that social bonding affects children do misbehavior. Therefore, to create social bonding in children, it is necessary to improve the pattern ofcare in the family, and supervision both in school and community environment.